Hypoxia-Induced Aquaporin-3 Changes Hepatocellular Carcinoma Cell Sensitivity to Sorafenib by Activating the PI3K/Akt Signaling Pathway [Retraction] - Malale K; Fu J; Qiu L; Zhan K; Gan X; Mei Z (Cancer Management and Research, 2021)
Malale K, Fu J, Qiu L, Zhan K, Gan X, Mei Z. Cancer Manag Res. 2020;12:4321–4333. The Editor and Publisher of Cancer Management and Research wish to retract the published article. Concerns were raised regarding the alleged duplication of Western Blot images in Figures 1D, 3A, 5A and 5B. The authors responded to our initial queries but were unable to provide a satisfactory explanation for the alleged duplication and could not provide satisfactory original data for their study. The Editor advised for the article to be retracted. The authors wish to apologise for this error. Our decision-making was informed by our policy on publishing ethics and integrity and the COPE guidelines on retraction. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”. This retraction relates to this paper